2021
DOI: 10.1021/acs.inorgchem.1c01646
|View full text |Cite
|
Sign up to set email alerts
|

A Ruthenium(II) Water Oxidation Catalyst Containing a pH-Responsive Ligand Framework

Abstract: The synthesis of a new Ru II -based water oxidation catalyst is presented, in which a nitrophenyl group is introduced into the backbone of dpp via a pH-sensitive imidazole bridge (dpp = 2,9-di-(2′-pyridyl)-1,10-phenanthroline). This modification had a pronounced effect on the photophysical properties and led to the appearance of a significant absorption band around 441 nm in the UV–vis spectrum upon formation of the monoprotonated species under neutral conditions. Theoretical investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Additionally, the phosphonic acid moieties may act as proton acceptor acting as internal base during the catalytic cycle accelerating deprotonation of the aquo ligand during catalysis. [29][30][31] These findings highlight the importance of the photosensitizer in photocatalytic processes. Based on the presented results a check list for the utilization of photosensitizers in WOC reactions could be implemented.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Additionally, the phosphonic acid moieties may act as proton acceptor acting as internal base during the catalytic cycle accelerating deprotonation of the aquo ligand during catalysis. [29][30][31] These findings highlight the importance of the photosensitizer in photocatalytic processes. Based on the presented results a check list for the utilization of photosensitizers in WOC reactions could be implemented.…”
Section: Discussionmentioning
confidence: 78%
“…The conditions were used based on a screening published earlier by our group. [30] The respective catalytic turnover numbers (TON) are given in Table 4. For compound 1 and [Ru(bpy) 3 ](PF 6 ) 2 (see Figure S9, SI) no catalytic oxygen evolution was observed under the given conditions.…”
Section: Water Oxidation Catalysismentioning
confidence: 99%
“…Thus, the potential dependence of p K a,Ox was modeled as normalp K normala , Ox ( E ) = prefix− 0.12 × E 1.1 0.25em normalV 0.059 0.25em normalV + 1.2 Note that this potential dependence on ITO has not been experimentally verified. Anchoring a Ru II water oxidation catalyst with a pH-sensitive visible absorption spectrum to the surface and monitoring its spectral behavior with an applied potential could provide useful insights. We also investigated models where p K a,Ox is independent of the potential E and found that such models could only reproduce the experimental data at higher pH, such as pH = 5, but not for the entire pH range (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…6 However, in practice, higher stability and catalytic efficiency have been observed for ruthenium (Ru) and iridium (Ir)-based catalysts, which have made them the most widely studied. 7 Earlier, we reported a highly active Ru-based water oxidation catalyst, [Ru(mcbp)(py) 2 ] (mcbp 2− = 2,6-bis(1-methyl-4-(carboxylate)-benzimidazol-2-yl)pyridine, py = pyridine, 1 in Fig. 1).…”
Section: Introductionmentioning
confidence: 99%